2021
DOI: 10.1038/s41392-021-00515-5
|View full text |Cite
|
Sign up to set email alerts
|

Unique and complementary suppression of cGAS-STING and RNA sensing- triggered innate immune responses by SARS-CoV-2 proteins

Abstract: The emergence of SARS-CoV-2 has resulted in the COVID-19 pandemic, leading to millions of infections and hundreds of thousands of human deaths. The efficient replication and population spread of SARS-CoV-2 indicates an effective evasion of human innate immune responses, although the viral proteins responsible for this immune evasion are not clear. In this study, we identified SARS-CoV-2 structural proteins, accessory proteins, and the main viral protease as potent inhibitors of host innate immune responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 47 publications
5
130
0
Order By: Relevance
“…ORF3a, a key accessory protein of SARS-CoV-2, is implicated in virulence, infectivity, ion channel formation, and virus release ( Issa et al, 2020 ). It has been reported that ORF3a is involved in autophagy inhibition ( Miao et al, 2021 ; Zhang et al, 2021 ), inflammasome activation ( Xu et al, 2020 ), nuclear factor-κB signaling suppression ( Rui et al, 2021 ), and apoptosis ( Ren et al, 2020 ). ORF3a possesses an N-terminal, a transmembrane (TM), and a C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…ORF3a, a key accessory protein of SARS-CoV-2, is implicated in virulence, infectivity, ion channel formation, and virus release ( Issa et al, 2020 ). It has been reported that ORF3a is involved in autophagy inhibition ( Miao et al, 2021 ; Zhang et al, 2021 ), inflammasome activation ( Xu et al, 2020 ), nuclear factor-κB signaling suppression ( Rui et al, 2021 ), and apoptosis ( Ren et al, 2020 ). ORF3a possesses an N-terminal, a transmembrane (TM), and a C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“… 9 11 Intriguingly, SARS-CoV-2 proteins such as ORF9b, ORF3a, and 3CL, were reported to inhibit the cGAS-STING pathway. 12 , 13 These viral antagonistic mechanisms may account for the dampened type-I IFN (IFN-I) levels in some severe COVID-19 cases. 14 Despite these inhibitory machineries exploited by the virus, overt IFN activation and inflammatory responses were still detected in SARS-CoV-2-infected animals 15 , 16 and peripheral blood or respiratory tract samples from COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…3CL protein inhibit K63-ubiquitin-mediated modification of STING and also decreases the function of NF-kB. Interestingly in the study that reported this results, both Orf3a and 3CL did not interfered with IRF3 activity [ 109 ].…”
Section: The Mtdna Receptors and Their Role In Inflammatory Processes - Do They Constitute A Possible Link With Sars-cov-2?mentioning
confidence: 93%
“…Regarding cGAS, SARS-CoV-2 proteins Orf3a and 3CL are able to interact and inhibit cGAS-STING activity. Orf3a bind to STING independently of it C or N terminal regions, and inhibit NF-kB activity and downstream gene expression [ 109 ]. 3CL protein inhibit K63-ubiquitin-mediated modification of STING and also decreases the function of NF-kB.…”
Section: The Mtdna Receptors and Their Role In Inflammatory Processes - Do They Constitute A Possible Link With Sars-cov-2?mentioning
confidence: 99%